The Asymptotic Behavior of Viscous Incompressible Fluid Small Oscillations with Solid Interacting Particles - Berezhnyi, M. A. (Журнал математичної фізики, аналізу, геометрії, 2007)
The motion of viscous incompressible fluid with a large number of smallsolid interacting particles is considered. The asymptotic behavior of smalloscillations of the system is studied, when the radii of particles, distancesbetween the nearest particles and their interaction power are decreased in the prescribed way. The equations describing the homogenized model of thesystem are derived. Mathematics Subject Classification: 35B27, 35Q30, 74Q10, 76M30, 76M50.